Implementation Of Life Safety Equipment On Board A Ship Operating At The Pontoon Pier At Gilimanuk Crossing Port Of Bali Province - Yohan Wibisono; Noor Sulistiyono; I Gst Ngr Gede Mahesa Putra (IWJ : Inland Waterways Journal, 2021)
Gilimanuk Crossing Port is organized and managed by PT. ASDP Indonesia Ferry (Persero), this crossing port serves 1 track with 50 Ro-Ro type ships (roll on - roll off) in operation. The high level of demand for crossing services, encourages the government to pay attention to all components related to crossing transportation, such as safety aspects that are one of the important components in crossing transportation. Including life safety equipment on board the ship as a precaution in case of an emergency. The method used in this study was carried out by comparing the existing state with the expected circumstances under the Regulation of the Director General of Sea Transportation NO: UM.008/9/20/DJPL – 12 on Technical Instructions for the Implementation of Indonesian-Flagged Non-Convention Vessel Standard (Non-Convention Vessel Standard Indonesian Flagged) Chapter IV Article 80. The author tried to analyze the problems that will later be drawn to be a solution or solution to the problem in an effort to increase supervision of the number and condition of passenger safety equipment on board ships operating at the pontoon dock at Gilimanuk Crossing Port of Bali Province.